Heavy metal bioabsorption capacity of intestinal helminths in urban rats. - Salma Teimoori; Aliakbar Sabour Yaraghi; Mahsa Sadat Makki; Farideh Shahbazi; Shahrokh Nazmara; Mohhamad Bagher Rokni; Alireza Mesdaghinia; Abdoreza Salahi Moghaddam; Mostafa Hosseini; Arash Rakhshanpour; Gholamreza Mowlavi (Tehran University of Medical Sciences, 2014)
The aim of the present study was to evaluate the capability of helminths to absorb heavy metals in comparison with that of the host tissues.We compared the concentration of cadmium (Cd) and chromium (Cr) in urban rats and in their harboring helminthes -Moniliformis moniliformis, Hymenolepis diminuta and larval stage of Taenia taenaeiformis (Cysticercus fasciolaris). The heavy metal absorption was evaluated in 1g wet weight of parasites and tissues digested in nitric acid, using Inductivity Coupled Plasma (ICP_OES).A higher concentration of heavy metals was revealed in the helminths than in the host tissues. Bioconcentration factor (BF= C in parasite/C in tissue) for both Cd and Cr absorption was more than 10-fold higher in M. moniliformis than in the three compared host tissues. The BF of Cd in M. moniliformis compared to the liver, kidney and muscle of the host was 9.16, 14.14 and 17.09, respectively. BF in Cr in the same parasite and the same host tissues ranged from 10.67, 7.06 and 4.6. High level of absorption in H. diminuta was significantly likewise; the individual BF of Cd and Cr in H. diminuta compared to the liver, kidney and muscle of the hosts was 4.95, 5.94 and 4.67 vs. 2.67, 11.56 and 5.59. The mean concentration of Cd and Cr in C. fasciolaris was also significantly higher than that in the rat livers (P